The Red Sea from Byzantium to the Caliphate : AD 500-1000 - Power, Timothy, 1979- (Cairo ; New York : American University in Cairo Press, 2012)
"This book examines the historic process traditionally referred to as the fall of Rome and the rise of Islam from the perspective of the Red Sea, a strategic waterway linking the Mediterranean to the Indian Ocean and a distinct region incorporating Africa with Arabia"--Dust jacket flap.
Includes bibliographical references (p. 279-356) and index.
Keywords: Red Sea -- History